Libraskê: Development of a Karaoke-Inspired Serious Game to Support Engagement and Dissemination of Brazilian Sign Language - Lima, Manuella A.; Araújo, Tiago M. U. de; Toscano, Rafael; Omaia, Derzu; Costa, Rostand E. O.; Silva, Vinícius G.; Silva, Diego L. R. da (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2025.9667, 2025)
Introduction: Accessibility remains a challenge in the entertainment industry, especially for the Deaf community, which often faces barriers due to limited fluency in written language and reliance on sign language as a primary form of communication. Objective: Develop and evaluate Libraskê, a game that combines Brazilian Sign Language (Libras) with karaoke elements to promote learning and dissemination of Libras. Methodology: In the game, a 3D avatar performs signs for selected song lyrics using VLibras. Players replicate the signs, which are captured and analyzed through computer vision techniques to generate performance scores. Results: An exploratory study involving Deaf and hearing participants showed promising engagement, suggesting the game’s potential as an inclusive tool for entertainment and Libras education.